2023
DOI: 10.3390/technologies11050120
|View full text |Cite
|
Sign up to set email alerts
|

Using Simple Interactive Technology to Help People with Intellectual and Visual Disabilities Exercise Functional Physical Responses: A Case Series Study

Giulio E. Lancioni,
Gloria Alberti,
Chiara Filippini
et al.

Abstract: The study assessed a new interactive technology system for helping six people with intellectual and visual disabilities exercise relevant physical responses embedded within a fairly straightforward activity (i.e., placing objects in containers). Activity responses consisted of the participants taking objects from the floor or a low shelf and placing those objects in a container high up in front of them (thus bending their body and legs and stretching their arms and hands). The technology involved a portable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Another research carried out in 2023 by Lancioni et al analysed the effects of long-term physical exercise programs on health and motor skills in youths with an intellectual disability. They concluded that physical exercise programs significantly improved balance, muscle strength, and agility (Lancioni et al, 2023). A different study focused on the effects of a workout routine on functional capacity and the quality of life in teenagers with an intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…Another research carried out in 2023 by Lancioni et al analysed the effects of long-term physical exercise programs on health and motor skills in youths with an intellectual disability. They concluded that physical exercise programs significantly improved balance, muscle strength, and agility (Lancioni et al, 2023). A different study focused on the effects of a workout routine on functional capacity and the quality of life in teenagers with an intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…Another research carried out in 2023 by Lancioni et al analysed the effects of long-term physical exercise programs on health and motor skills in youths with an intellectual disability. They concluded that physical exercise programs significantly improved balance, muscle strength, and agility [5]. A different study focused on the effects of a workout routine on functional capacity and the quality of life in teenagers with an intellectual disability.…”
Section: Introductionmentioning
confidence: 99%